CrowdSLR: a tool to support the use of crowdsourcing in systematic literature reviews - Santos, Vinicius; Iwazaki, Anderson; Souza, Érica; Felizardo, Katia; Vijaykumar, Nandamudi (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2021: Anais do XXXV Simpósio Brasileiro de Engenharia de Software, 2021)
Systematic Literature Reviews (SLR) have been used by Software Engineering (SE) community to produce reliable scientific evidence. An SLR process can be exhaustive and time-consuming, therefore, many approaches have been proposed to reduce time and efforts during the SLR conduction process. Although the SLR process is amenable to automation, nowadays full automation is not yet possible. An alternative to reduce time and efforts in SLR conduction is the use of crowdsourcing. However, there is no crowdsourcing tool to support a crowd-based SLR process. In this context, we present CrowdSLR, a tool to support the application of crowdsourcing in SLR during the selection of primary studies. Furthermore, we present its main features, potential users, and the architecture that was implemented to allow researchers to adopt this tool. The results of the CrowdSLR application indicate that the tool is able to provide the use crowdsourcing during the SLR selection process. The results that the proposed tool, indeed, show a significant improvement in the crowdsourcing approach in terms of time and effort to facilitate the SLR selection activity. Demo Video: https://youtu.be/UoQTC-R-Mv0